Biological control of bacterial wilt pathogen (Ralstonia solanacearum) of tomato using endophytic bacteria is one of the alternative control methods to support sustainable agriculture. This study was conducted to select and characterize endophytic bacteria isolated from healthy tomato stems and to test their ability to promote plant growth and suppress bacterial wilt disease. Among 49 isolates successfully isolated, 41 were non-plant pathogenic. Green house test on six selected isolates based on - ABDJAD ASIH NAWANGSIH; IKA DAMAYANTI; SURYO WIYONO; JUANG GEMA KARTIKA (Bogor Agricultural University, Indonesia, 2011)
Biological control of bacterial wilt pathogen (Ralstonia solanacearum) of tomato using endophytic bacteria is one of the alternative control methods to support sustainable agriculture. This study was conducted to select and characterize endophytic bacteria isolated from healthy tomato stems and to test their ability to promote plant growth and suppress bacterial wilt disease. Among 49 isolates successfully isolated, 41 were non-plant pathogenic. Green house test on six selected isolates based on antagonistic effect on R. solanacearum or ability to suppress R. solanacearum population in dual culture assays obtained BC4 and BL10 isolates as promising biocontrol agents. At six weeks after transplanting, plants treated with BC4 isolate showed significantly lower disease incidence (33%) than that of control (83%). Plants height was not significantly affected by endophytic bacterial treatments. Based on 16S rRNA sequence, BC4 isolate had 97% similarity with Staphylococcus epidermidis (accession number EU834240.1), while isolate BL10 had 98% similarity with Bacillus amyloliquefaciens strain JK-SD002 (accession number AB547229.1).